Rodríguez González, Mariano: Filosofía de la Mente. Madrid: Ediciones Complutense, 2021, pp. 287. - Alonso Rodríguez, Blas (Logos. Anales del Seminario de Metafísica, 2022)
Reseña de la obra de Rodríguez González, Mariano: Filosofía de la Mente. Madrid: Ediciones Complutense, 2021, pp. 287.